The Malaysian sukuk model : an exploratory study of its implementation in Bangladesh capital market - Hoque, Muhammad Nazmul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Malaysia has made commendable progress in developing the Sukuk Market. Sukuk also known as Islamic Bond, are widely used in meeting the capital needs of the government and corporate sectors. The present research aims to examine what makes Malaysia as an epicenter in Sukuk Market internationally. A thorough study was conducted on various aspects that give impetus to the subject matter. The objective of this study is to describe the Sukuk structures underlying the Islamic principles and identify how Malaysian experts evaluate the Sukuk in the Malaysian capital market, as well as explain the impact of the implementation of Sukuk and provide the possible solutions for the issues that might arise from Sharia'h perspective. Thus, this research is an exploratory study of the Malaysian Sukuk Model in order to implement it in Bangladesh Capital Market. The method that has been used in this research is qualitative research methodology. The study has also employed a comparative method when dealing with the different opinions of scholars. Using a self-designed questionnaire, the aims of this interview was to know their opinions about its structure. The findings indicate that Malaysian Sukuk structure is positively associated with their perceived acceptability of implementation of Sukuk in Bangladesh Capital Market. The significant factor that influences the level of acceptability is professional qualification of the experts. Since the issue of Sukuk is considered new in Bangladesh, perhaps the exposure on the implementation might be a better understanding on the structuring Sukuk in Bangladesh Capital Market.